Peran Mediasi Kepuasan Kerja pada Pengaruh Keadilan Distributif dan Keadilan Prosedural terhadap Komitmen Afektif Studi Pada Kantor Dinas Koperasi dan Usaha Mikro Kabupaten Pacitan - Epsilandri Septyarini; Bahtiar Nur Syahbana (Jurnal Manajemen, 2021)
This study aims to determine (1) the effect of distributive justice on job satisfaction and, (2) the effect of procedural justice on job satisfaction (3) the effect of job satisfaction on affective commitmnent (4) the effect of distributive justice on affective commitmnet (5) the effect of procedural justice on affective commitment. Research took sample by applying nonprobability sampling with saturated sample. The sample in this study were 40 employee of Dinas Koperasi dan Usaha Mikro Kabupaten Pacitan. The data collection method uses a questionnaire method that is distributed using the Purposive Sampling technique. In this research, data quality test, classical assumption test (normality test, multicollinearity test and heterokesdasticity test) are used, multiple linear regression analysis , sobel test, path analysis, and hypothesis testing. The research show that there is a positive significant relationship between distributive justice on job satisfaction, procedural justice on job satisfaction, procedural justice on affective commitment, job satisfaction on affective commitment, job satisfaction have a positive and significant effect on mediating between distributive justice and procedural justice on affective commitment. In the other result, this research found that there is no positive and significant effect between distributive justice on affective commitment. Keywords : distributive justice, procedural justice, job satisfaction, affective commitment